2019
DOI: 10.1016/j.actamat.2018.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Growth, interfacial microstructure and optical properties of NiO thin films with various types of texture

Abstract: NiO thin films with random, fiber and in-plane textures have been successfully deposited at near room temperature by reactive magnetron sputtering on glass, silicon and Al 2 O 3 (0001) substrates. Self-texture related with the deposition conditions and crystallographic characters competes with the driving force from the matched substrate. Such a competition can be used to control the texture of thin films on matched substrates, especially when the promoting orientations from self-texture and substrate are diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 32 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…Electrical Characterization of Grown Thin Films and Heterojunction Diode. Figure 2a shows the XRD measurements of the single-crystalline films, manifesting (2̅ 01)-oriented β-Ga 2 O 3 and (111)-oriented cubic NiO films on c-plane sapphire, 38,39 whereas Figure 2b shows the measured RBS curves for thinner NiO and β-Ga 2 O 3 films on sapphire, confirming the stoichiometry of each layer and the well-defined interfaces. It can be seen that the Ni and Al signals overlap with that of Ga and O, respectively; the Ir and Ag signals originate from the metallic layer sputtered onto the sample before the RBS experiment in order to avoid electrostatic charging.…”
Section: Resultsmentioning
confidence: 66%
“…Electrical Characterization of Grown Thin Films and Heterojunction Diode. Figure 2a shows the XRD measurements of the single-crystalline films, manifesting (2̅ 01)-oriented β-Ga 2 O 3 and (111)-oriented cubic NiO films on c-plane sapphire, 38,39 whereas Figure 2b shows the measured RBS curves for thinner NiO and β-Ga 2 O 3 films on sapphire, confirming the stoichiometry of each layer and the well-defined interfaces. It can be seen that the Ni and Al signals overlap with that of Ga and O, respectively; the Ir and Ag signals originate from the metallic layer sputtered onto the sample before the RBS experiment in order to avoid electrostatic charging.…”
Section: Resultsmentioning
confidence: 66%
“…Wang et al emphasized the importance of understanding and controlling material texture since it influences mechanical and chemical properties. [28] Thermomechanical processing has been used on cast materials to change the texture and, as a result, the properties of the materials. [29] Wei et al have shown that AM offers much more flexibility in controlling the textures and properties of a material.…”
Section: Introductionmentioning
confidence: 99%
“…Intensive {111} diffraction peaks of NiO are clearly detected, indicating the high <111> orientation along the c-axis. Additionally, φ-scan diffractogram of the (200) (ψ = 54.7) plane shows six peaks with intervals of 60 • (see Figure 5b), which indicates the epitaxial growth of NiO thin films [37]. Epitaxial NiO thin films exhibit much stronger diffraction intensity and smaller full width at half maximum (FWHM) values than those on non-matched glass or Si substrates (see Figure 1), even though they are deposited at the same time.…”
Section: Microstructure Dependence Of Electrical Propertiesmentioning
confidence: 99%